GmSnRK1.1, a Sucrose Non-fermenting-1(SNF1)-Related Protein Kinase, Promotes Soybean Resistance to Phytophthora sojae - Wang, Le; Wang, Huiyu; He, Shengfu; Meng, Fanshan; Zhang, Chuanzhong; Fan, Sujie; Wu, Junjiang; Zhang, Shuzhen; Xu, Pengfei (Frontiers in Plant Science, 2019)
Phytophthora root and stem rot, a destructive disease of soybean [Glycine max (L.) Merr.], is caused by the oomycete Phytophthora sojae. However, how the disease resistance mechanisms of soybean respond to P. sojae infection remains unclear. Previously, we showed that GmWRKY31, which interacts with a sucrose nonfermenting-1(SNF1)-related protein kinase (SnRK), enhances resistance to P. sojae in soybean. Here, we report that the membrane-localized SnRK GmSnRK1.1 is involved in the soybean host response to P. sojae. The overexpression of GmSnRK1.1 (GmSnRK1.1-OE) increased soybean resistance to P. sojae, and the RNA interference (RNAi)-mediated silencing of GmSnRK1.1 (GmSnRK1.1-R) reduced resistance to P. sojae. Moreover, the activities and transcript levels of the antioxidant enzymes superoxide dismutase and peroxidase were markedly higher in the GmSnRK1.1-OE transgenic soybean plants than in the wild type (WT), but were reduced in the GmSnRK1.1-R plants. Several isoflavonoid phytoalexins related genes GmPAL, GmIFR, Gm4CL and GmCHS were significantly higher in ‘Suinong 10’ and GmSnRK1.1-OE lines than these in ‘Dongnong 50’, and were significantly lower in GmSnRK1.1-R lines. In addition, the accumulation of salicylic acid (SA) and the expression level of the SA biosynthesis-related gene were significantly higher in the GmSnRK1.1-OE plants than in the WT and GmSnRK1.1-R plants. Moreover, SA biosynthesis inhibitor treated GmSnRK1.1-R lines plants displayed clearly increased pathogen biomass compared with H2O-treated plants after 24 h post-inoculation. These results showed that GmSnRK1.1 positively regulates soybean resistance to P. sojae, potentially functioning via effects on the expression of SA-related genes and increased accumulation of SA.